Chromosome engineering in zygotes with CRISPR/Cas9. Issue 2 (25th January 2016) - Boroviak, Katharina; Doe, Brendan; Banerjee, Ruby; Yang, Fengtang; Bradley, Allan
SUMMARY: Deletions, duplications, and inversions of large genomic regions covering several genes are an important class of disease causing variants in humans. Modeling these structural variants in mice requires multistep processes in ES cells, which has limited their availability. Mutant mice containing small insertions, deletions, and single nucleotide polymorphisms can be reliably generated using CRISPR/Cas9 directly in mouse zygotes. Large structural variants can be generated using CRISPR/Cas9 in ES cells, but it has not been possible to generate these directly in zygotes. We now demonstrate the direct generation of deletions, duplications and inversions of up to one million base pairs by zygote injection. genesis 54:78–85, 2016. © 2016 The Authors. Genesis Published by Wiley Periodicals, Inc.